SIPRI Yearbook 2017 - MAGIERA, Maciej (Przegląd Strategiczny, 2018)
The study is dedicated to the most important trends confirmed by current knowledge in the SIPRI Yearbook 2017. SIPRI annually issues a study which shows a comprehensive picture of the activity of international actors in terms of world military expenditure, international arms transfers, arms production, nuclear forces, armed conflicts and multilateral peace operations, as well as the promotion of security and development.